Impact of spacer on membrane gas separation performance - Foo, K.; Lin, W.; Goh, P.S.; A.L., Ahmad; Liang, Y. Y. (Elsevier Ltd, 2023)
Mixing in gas separation membranes has received much less attention than in membrane liquid separation because gas molecules have much smaller viscosity, allowing them to diffuse easily through membranes without requiring significant flow mixing. However, due to advancements in membrane fabrication technologies aimed at improving material properties, concentration polarization (CP) might become an issue in gas separation due to enhanced membrane efficiency and permeability. Consequently, a 2D CFD analysis is conducted to evaluate the impact of spacer-induced mixing on membrane gas concentration polarization for typical CO2/CH4 gas separation. Results show that spacers generally enhance flux performance while reducing CP in the membrane channel when compared to the case without spacers. Furthermore, the effectiveness of spacer-flux-to-pressure-loss-ratio (SPFP) reaches a peak for a Reynolds number in the range of 5 <Reh< 200 because of the trade-off between flux and pressure drop. This mixing-induced flux enhancement is most effective under high CP conditions (less mixing) within the membrane channel. Similarly, flux enhancement due to spacers can be observed as membrane selectivity, pressure ratio and feed gas concentration increase due to enhanced CP.